2015
DOI: 10.1111/evj.12445
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of equine metabolic syndrome: A clinical case series

Abstract: A diet and exercise programme tailored to the needs of the individual animal and implemented by the owner results in weight loss accompanied by improvements in insulin sensitivity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
43
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(47 citation statements)
references
References 45 publications
1
43
1
Order By: Relevance
“…11 Similarly, horses that lose weight and adiposity can show improved insulin sensitivity. 15 These findings mirror the situation in human medicine, where improved diet, weight loss, and exercise result in increased insulin sensitivity in individuals with type 2 diabetes mellitus (noninsulin-dependent diabetes mellitus) and pre-diabetic states. 15 In human medicine, diagnostic testing of glucose metabolism is performed on subjects who have fasted for at least 8 hours.…”
mentioning
confidence: 65%
See 1 more Smart Citation
“…11 Similarly, horses that lose weight and adiposity can show improved insulin sensitivity. 15 These findings mirror the situation in human medicine, where improved diet, weight loss, and exercise result in increased insulin sensitivity in individuals with type 2 diabetes mellitus (noninsulin-dependent diabetes mellitus) and pre-diabetic states. 15 In human medicine, diagnostic testing of glucose metabolism is performed on subjects who have fasted for at least 8 hours.…”
mentioning
confidence: 65%
“…15 These findings mirror the situation in human medicine, where improved diet, weight loss, and exercise result in increased insulin sensitivity in individuals with type 2 diabetes mellitus (noninsulin-dependent diabetes mellitus) and pre-diabetic states. 15 In human medicine, diagnostic testing of glucose metabolism is performed on subjects who have fasted for at least 8 hours. 16 Published protocols for the OST and IRT in horses have been inconsistent when specifying whether or not the animals should be fasted before the tests are performed, and, if so, for how long.…”
mentioning
confidence: 65%
“…Parenteral delivery of exogenous glucose, insulin, or both has the advantage of decreasing variability associated with gastrointestinal transit and absorption but also omits some possibly important elements of ID including incretin effects. Nevertheless, such tests allow focus on specific elements of ID such as IR and have been successfully used to diagnose and monitor EMS in clinical and research settings …”
Section: Laboratory Diagnosismentioning
confidence: 99%
“…The combined glucose insulin test (CGIT) is based on injection of 150 mg/kg BM glucose IV, directly followed by 0.1 IU/kg BM neutral (regular) insulin IV . In a shortened protocol, both insulin and glucose are measured in the basal sample and after 45 and 75 minutes . Typical healthy horses show a biphasic blood glucose curve starting with hyperglycemia, followed by a negative phase in which glucose drops below the initial baseline value.…”
Section: Laboratory Diagnosismentioning
confidence: 99%
“…Within the Pony Club system, owners and riders receive a considerable amount of basic information on horse care and management. It has recently been shown that, with appropriate diet and exercise management, insulin dysregulation in horses and ponies with EMS can be minimised . Presumably, this will also reduce the risk of laminitis, although this has not yet been proven in a full prospective study.…”
Section: Discussionmentioning
confidence: 99%